2016
DOI: 10.1016/j.joca.2016.05.017
|View full text |Cite
|
Sign up to set email alerts
|

A novel rat model for subchondral microdamage in acute knee injury: a potential mechanism in post-traumatic osteoarthritis

Abstract: This study shows that our novel model can be used to study subchondral microdamage after ACL-rupture, and its association with localized remodeling. Cartilage degeneration, on a similar time-scale to other models, is also a feature of this system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 56 publications
0
40
0
1
Order By: Relevance
“…We chose this model in rats because of the technical ease in injecting the knees of these animals and because correction of an induced lesion would better mimic the situation in humans. The procedure was performed under anesthesia (1–3% isoflurane) as previously described68. All experimental groups of rats, as described below, consisted of 3 rats and each experimental group was repeated once (total of 6 rats per experimental group).…”
Section: Methodsmentioning
confidence: 99%
“…We chose this model in rats because of the technical ease in injecting the knees of these animals and because correction of an induced lesion would better mimic the situation in humans. The procedure was performed under anesthesia (1–3% isoflurane) as previously described68. All experimental groups of rats, as described below, consisted of 3 rats and each experimental group was repeated once (total of 6 rats per experimental group).…”
Section: Methodsmentioning
confidence: 99%
“…In the last 10 years, multiple non‐invasive ACL rupture models have been developed. These models have primarily used mice and rabbits, with a limited number of studies involving rats . Despite being relatively understudied, there are advantages to establishing this injury model in rats, such as their amenability to behavioral tests and their larger size, which can accommodate certain imaging modalities and therapeutic interventions .…”
mentioning
confidence: 99%
“…Despite being relatively understudied, there are advantages to establishing this injury model in rats, such as their amenability to behavioral tests and their larger size, which can accommodate certain imaging modalities and therapeutic interventions . Even within the few studies using rats, different structural outcomes have been observed following ACL rupture, ranging from cartilage degeneration to cartilage thickening . Additionally, the characterization of the inflammatory response to this injury has been scarcely studied, with only one recent evaluation of immune cell involvement and cytokine profile following injury in mice reported .…”
mentioning
confidence: 99%
“…The authors contrast these methods and note that each provides an opportunity to study a particular aspect of PTOA . Our laboratory has developed a noninvasive rat model, which provides an opportunity to study subchondral microdamage . Using this model, we can determine the role of microdamage and its subsequent repair by remodeling in PTOA development via altered bone/cartilage crosstalk.…”
Section: Animal Models For Ptoamentioning
confidence: 99%
“…64 Our laboratory has developed a noninvasive rat model, which provides an opportunity to study subchondral microdamage. 69 Using this model, we can determine the role of microdamage and its subsequent repair by remodeling in PTOA development via altered bone/cartilage crosstalk. Other research groups have also used the rat for OA studies, inducing joint disease by surgical intervention or by ACL rupture.…”
Section: Animal Models For Ptoamentioning
confidence: 99%